5.7 GHz GalnP/GaAs HBT sub-harmonic gilbert downconverter with octet-phase LO generator - Wu, T. -H.; Meng, C.; Wu, T. -H. (My University, 2006)
A 5.7 GHz GaInP/GaAs heterojunction bipolar transistor (HBT) sub-harmonic Gilbert downconversion mixer with octet-phase LO generator is demonstrated. The conversion gain is 15 dB, IP1dB is - 13 dBm, IIP3 is 0 dBm, and IIP2 is 24 dBm when the LO power equals 3 dBm. The measured IF quadrature output waveforms indicate that the phase difference between the in-phase and quadrature-phase output channels is only 1.3 degrees.